The Profile of Human Milk Metabolome, Cytokines, and Antibodies in Inflammatory Bowel Diseases Versus Healthy Mothers, and Potential Impact on the Newborn. (12th November 2018) - Meng, Xuanyi; Dunsmore, Garett; Koleva, Petya; Elloumi, Yesmine; Wu, Richard You; Sutton, Reed Taylor; Ambrosio, Lindsy; Hotte, Naomi; Nguyen, Vivian; Madsen, Karen L; Dieleman, Levinus A; Chen, Hongbing; et al.
Abstract: Background and Aims: For women with inflammatory bowel disease [IBD], it is not very well known how IBD or IBD treatment affects their breast milk components. We aimed to investigate whether breast milk composition differs in healthy control [HC] versus IBD mothers in terms of antibodies, cytokines, and metabolite, s to identify potential impact of IBD breast milk on neonatal immune system. Methods: Breast milk specimens from HC [ n = 17] and IBD [ n = 31 for Crohn's disease [CD]; and n = 41 for ulcerative colitis [UC]; were collected at 3 and 6 months postpartum [PP3] and [PP6], respectively. Faecal samples were also collected. Cytokines and immunoglobulins [IgA/IgG/IgE] were analysed by multiplex Meso Scale Discovery [MSD] and commercial kits. Moreover, breast milk metabolites were analysed by 1 H nuclear magnetic resonance [NMR]. Results: We found that breast milk from IBD mothers showed significantly lower levels of IgA, sugar metabolite [lactose], and 2-aminobutyrate. In contrast, we observed that breast milk from mothers with IBD had increased levels of pro-inflammatory cytokines and higher energy metabolites [lactate and succinate] than milk from healthy mothers. In addition, we noticed that the type of treatment [5-aminosalicylic acid versus biologics] influenced the milk cytokines and metabolites profile. Conclusions: The reduction in immunoprotective components of IBD breast milk such as sIgA and lactose theoretically may modulate the potential protective effects of breastfeeding. On the other hand, presence of higher levels of pro-inflammatory cytokines, lactate, and succinate may predispose the offspring to an inflammatory condition or impact on the gut microbiome. Better understanding of the role of succinate in infants and its potential effects on microbiome or mucosal immunity merits further investigations.